Profiling sprint mechanics by leg preference and position in Rugby Union athletes - Brown, S. R.; Brughelli, M.; Cross, M. R. (International Journal of Sports Medicine, 2016)
Lower-extremity power characteristics are central to performance in rugby. However little is known regarding the effects of leg preference and playing position on sprint mechanics. The purpose of this study was to profile sprint kinetics and kinematics in rugby union athletes and compare between legs and between positions. Thirty male academy-level rugby union athletes, separated into forwards (n=15) and backs (n=15), participated in this cross-sectional analysis. Non-motorised treadmill ergometry was used to evaluate peak relative vertical (FV) and horizontal (FH) force and peak relative power (Pmax) of the preferred and non-preferred legs during maximal sprinting. The non-preferred leg of the forwards produced less FV, FH and Pmax than the preferred leg during acceleration (ES=-0.32, - 0.58 and - 0.67) and maximal velocity (ES=- 0.50, - 0.65 and - 0.60). Backs produced more FV, FH and Pmax than the forwards during initial acceleration (ES=0.51, 1.58 and 1.30) but less at maximal velocity (ES=- 0.74, -0.79 and - 0.81). Backs had faster split times at 2, 5, 10 and 15 m (ES=-1.03, -0.82, -0.63 and -0.50) but slower times at 35 and 40?m (ES=0.78 and 1.10) compared with forwards. Forwards produced larger sprint kinetics compared with backs, but also larger lower-extremity imbalances; potentially reducing sprint efficiency and/or increasing injury risk.